The Leadership and Access to Technology-Based Health Information as A Public Health Promotion Strategy - Lolong, Rima Fien; Rawis, Joulanda A.M.; Tambingon, Henny N.; Kambey, Joseph (JR Education, 2023)
This article discusses the role of leadership in promoting public health through access to technology-based health information. With the increasing use of technology in healthcare, it is important to ensure that individuals have access to accurate and reliable health information. The article argues that effective leadership is necessary to facilitate the dissemination of health information through technology and to ensure that individuals have the skills and resources to access this information. The article also highlights the importance of addressing barriers to access, such as lack of internet connectivity and limited digital literacy. The article concludes that by prioritizing access to technology-based health information and fostering effective leadership in this area, public health promotion efforts can be strengthened and improved